PEMBERIAN KOMBINASI PUPUK DAUN GANDASIL D DENGAN PUPUK NANO-SILIKA TERHADAP PERTUMBUHAN BIBIT MANGROVE (Bruguiera gymnorrhiza) - Widi Hastuti; Erma Prihastanti; Sri Haryanti; Agus Subagyo (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2016)
Increased damage to mangrove forests are increasingly threatened mangrove making function is reduced. Sustainability of mangrove forest areas depend on seedlings. Mangrove Nutrition is important, especially during the breeding. The addition of fertilizer leaves by spraying the leaves can maximize fertilizer efficiency. Dry environmental conditions and high stress on the lives of mangroves to make silica used in improving the sustainability of mangrove. This research aim to analyze the effect of the combination of Gandasil D leaf fertilizer and nanosilica fertilizer and analyze the optimal concentration of combination Gandasil D leaf fertilizer and nanosilica fertilizer in mangrove plant seeds (Bruguiera gymnorrhiza) growth. Research conducted with Complete Random Design with one factor. There are 6 treatments: control, leaf fertilizer 75% + 25% Nanosilica, leaf fertilizer 50% + 50%, leaf fertilizer 25% + 75% Nanosilica, Nanosilica 100%, leaf fertilizer 100%. The experiments was conducted with 5 replicates. The parameters observed, amount of leaves, leaf area, high of plants, amount of chlorophyll and leaf color. Supporting parameters include temperature, pH, moisture and air. Analysis of the data used is ANOVA followed by further test of Duncan Multiple Range Test (DMRT) at the 95% significance level. The results indicate that the combination of leaf fertilizer and Nanosilica effect on growth (Bruguiera gymnorrhiza). The combination of optimum fertilization in increasing growth that is 50% leaf fertilizer and 50% Nanosilica. Keywords: mangrove, Bruguiera gymnorrhiza, Gandasil D leaf fertilizer, nanosilika fertilizer